Analgesic Efficacy and Mode of Action of a Selective Small Molecule Angiotensin II Type 2 Receptor Antagonist in a Rat Model of Prostate Cancer‐Induced Bone Pain. Issue 1 (30th October 2013) - Muralidharan, Arjun; Wyse, Bruce D.; Smith, Maree T.
Abstract Objective The pathobiology of prostate cancer (PCa)‐induced bone pain (PCIBP) has both inflammatory and neuropathic components. Previously, we showed that small molecule angiotensin II type 2 receptor (AT2R) antagonists with >1, 000‐fold selectivity over the angiotensin II type 1 receptor produced dose‐dependent analgesia in a rat model of neuropathic pain. Here, we assessed the analgesic efficacy and mode of action of the AT2R antagonist, EMA200, in a rat model of PCIBP. Methods At 14–21 days after unilateral intratibial injection of AT3B PCa cells, rats exhibiting hindpaw hypersensitivity received single intravenous bolus doses of EMA200 (0.3–10 mg/kg) or vehicle, and analgesic efficacy was assessed. The mode of action was investigated using immunohistochemical, Western blot, and/or molecular biological methods in lumbar dorsal root ganglia (DRGs) removed from drug‐naïve and EMA200‐treated PCIBP rats relative to sham‐control rats. Results Intravenous bolus doses of EMA200 produced dose‐dependent analgesia in PCIBP rats. Lumbar DRG levels of angiotensin II, nerve growth factor (NGF), tyrosine kinase A (TrkA), phospho‐p38 mitogen‐activated protein kinase (MAPK), and phospho‐p44/p42 MAPK, but not the AT2R, were increased significantly (P < 0.05) in PCIBP rats, c.f. the corresponding levels for sham controls. EMA200 produced analgesia in PCIBP rats by reducing elevated angiotensin II levels in the lumbar DRGs to attenuate augmented angiotensin II/AT2R signaling. This in turn reduced augmented NGF/TrkA signaling in the lumbar DRGs. The net result was inhibition of p38 MAPK and p44/p42 MAPK activation. Conclusion Small molecule AT2R antagonists are worthy of further investigation as novel analgesics for relief of intractable PCIBP and other pain types where hyperalgesia worsens symptoms.